2012
DOI: 10.1530/rep-11-0245
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal testicular development in mouse species with different levels of sperm competition

Abstract: Postcopulatory sexual selection leads to an increase in sperm numbers which is partly the result of an increase in relative testes mass and could also be the consequence of changes in testis architecture or function. Very little is known regarding developmental changes during the first spermatogenic wave that may lead to enhanced spermatogenic efficiency and increased sperm production. We examined testicular development after birth in four mouse species with different sperm competition levels to assess changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 71 publications
4
49
0
Order By: Relevance
“…Before 10 dpp, testes of the mouse (Mus musculus) contain mostly spermatogonia. Between 21 and 24 dpp (weaning ages), spermatocytes become the most abundant cell type, round spermatids develops as the most advanced germ cells, and in adults, spermatids are a predominant cell type stage [35, 36]. Based on the changes in types of spermatogenic cells, qPCR was performed at the stage of spermatogonia (10 dpp), spermatocytes and round spermatids (21 dpp), and spermatids (91 dpp).…”
Section: Discussionmentioning
confidence: 99%
“…Before 10 dpp, testes of the mouse (Mus musculus) contain mostly spermatogonia. Between 21 and 24 dpp (weaning ages), spermatocytes become the most abundant cell type, round spermatids develops as the most advanced germ cells, and in adults, spermatids are a predominant cell type stage [35, 36]. Based on the changes in types of spermatogenic cells, qPCR was performed at the stage of spermatogonia (10 dpp), spermatocytes and round spermatids (21 dpp), and spermatids (91 dpp).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has been a revival of interest in considering the amount of spermatogenic tissue the testis contains. In New World blackbirds (Icteridae) (Lüpold et al, 2009b), the Australian passerine family Maluridae (Rowe & Pruett-Jones, 2011), and in four closely related mouse species (Montoto et al, 2012), those species subject to high levels of sperm competition have been found to exhibit testes containing a higher proportion of spermatogenic tissue. This demonstrates that in order to attain a higher spermatogenic activity, sperm competition can select not only for a larger, but also for a more efficient testis (see also Wistuba et al, 2003;Luetjens, Weinbauer & Wistuba, 2005;and Table 1 for brief discussion of the various definitions of 'spermatogenic efficiency').…”
Section: How Does the Testis Maximise Sperm Output?mentioning
confidence: 99%
“…The first meiotic division into spermatocytes occurs within 14-20 days (Montoto et al, 2012). Only germ cells are observed in the canine testis after 1-3 months; the size of the tubules and the number of germ cells increase over time (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mice, dogs, and pigs, Sertoli cells are more abundant than germ cells in the perinatal or neonatal period. After the appearance of the first spermatocytes around the infantile or pubertal period, the number of Sertoli cells is smaller than in the neonatal or perinatal period; the seminiferous cord also grows, and the number of germ cells increases in the perinatal or neonatal period (Lee et al, 2014;Montoto et al, 2012;Sharpe et al, 2003) (Supplementary Fig. S1A-C).…”
Section: Discussionmentioning
confidence: 99%